2012
DOI: 10.1097/mcg.0b013e3182684d71
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Association of 2 Probiotic Strains Formulated in a Slow Release Vaginal Product, in Women Affected by Vulvovaginal Candidiasis

Abstract: VVC has a very high incidence as 70% to 75% of women report at least 1 episode during the life. Many treatments are currently available but, despite a relatively high effectiveness in the relief of symptoms typically associated with acute infections, they are generally unable to offer a long-term protective barrier against possible recurrences. This study demonstrated the ability of ActiCand 30 to not only solve Candida infections in a very high percentage of women, but also to exert a long-term physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 30 publications
1
53
0
5
Order By: Relevance
“…S1A and B in the supplemental material). Nonlinear regression of the dose-response curves found significantly different values for the IC 50 (concentration required to inhibit growth rate by 50%) of each acid tested. In particular, butyric acid had the most potent activity against C. albicans growth, followed by propionic, acetic, and lactic acid ( Fig.…”
Section: Weak Organic Acids Are Fungistatic Under Physiological Condimentioning
confidence: 99%
See 1 more Smart Citation
“…S1A and B in the supplemental material). Nonlinear regression of the dose-response curves found significantly different values for the IC 50 (concentration required to inhibit growth rate by 50%) of each acid tested. In particular, butyric acid had the most potent activity against C. albicans growth, followed by propionic, acetic, and lactic acid ( Fig.…”
Section: Weak Organic Acids Are Fungistatic Under Physiological Condimentioning
confidence: 99%
“…To understand the genetic requirements of this fungus for its response to WOAs, we took advantage of a previously published library of C. albicans mutant strains, each of which had had 1 of 165 transcription factors (TFs) deleted (26). The library was subjected to robotically assisted high-throughput growth assays, with the medium adjusted to pH 5.5 and each compound used at its respective IC 50 (Fig. 3).…”
Section: Weak Organic Acids Are Fungistatic Under Physiological Condimentioning
confidence: 99%
“…They contended though that empirical use of probiotics may be considered in women with RVVC, especially for those who have adverse effects from or contraindications for the use of antifungal agents, since adverse effects of probiotics are very rare [147]. In a more recent study Vicariotto et al [120] reported that probiotics reduce recurrences [120]. However their sample size was also very small.…”
Section: Discussionmentioning
confidence: 97%
“…Their mode of action is thought to be modulation of the inflammatory process rather than competitive effect with the yeast [119]. In a recent study Vicariotto et al [120] reported that probiotics reduce recurrences [120].…”
Section: E) Alternative Treatmentmentioning
confidence: 99%
“…as a single therapy to improve the vaginal ecosystem status and to treat and/or prevent BV, CVV, aerobic vaginitis (AV) and trichomoniasis [66,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94]. In most of the studies, commercial probiotic products or new potential probiotic formulations were vaginally administered.…”
Section: Clinical Studies Of Urogenital Probioticsmentioning
confidence: 99%